Gaya Bahasa Dalam Puisi Kyonen No Kyou Karya Kaneko Misuzu - Nova Antari, Ni Made; Luhur Wedayanti, Ni Putu; Rauh Artana, I Nyoman (Humanis, 2016)
This study entitled “Stylistics Found in Kaneko Misuzu’s Poem Kyonen no Kyou” focused on identifying and understanding kinds and functions of language style found in this literary work. Stylistic theory proposed by Al-Ma’ ruf (2009) and rhetoric theory proposed by Seto (2002) were applied. As a result, it was identified that Kyonen no Kyou poem is expressed by the author clearly and in detail by using characteristic style and diction related to children. The language style is functioned to emphasize respect, to raise certain meaning and context, and to concretize speech.